Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar pada Materi Sistem Persamaan Linear Dua Variabel - Aisun, Putri; Nurhayadi, Nurhayadi; Idris, Mustamin; Rizal, Muh. (Jurnal Pendidikan Matematika : Judika Education, 2024)
This study describes Classroom Action Research (CAR) through the application of the Problem Based Learning model which aims to improve student learning outcomes in the material of two-variable linear equation systems. The subjects of this study were students of class VIIIA of SMP BK Kalawara. The results of the study showed that there was an increase in student learning outcomes in the material of two-variable linear equation systems through Classroom Action Research using the method of the stages of problem based learning. The stages are: 1) Orienting students to the problem, 2) Organizing students to learn, 3) Guiding individual/group investigations, 4) Reading and presenting the results of the work, and 5) Analyzing and finding the problem-solving process. The increase in student learning outcomes has met the indicators of successful actions in cycles I and II, obtained from data from the results of student analysis activities in each cycle that the items in the category are quite good, those in the good category increase to very good and those in the very good category can be sustainable. The results from cycle I to cycle II increased due to improvements. Conclusion, the application of the problem based learning model can improve the learning outcomes of class VIIIA students of SMP BK Kalawara in the material of two-variable linear equation systems. Key Word: Classroom Action Research, Learning Outcomes, Problem Based Learning, Study Group